A Novel Method for Location Privacy Protection in LBS Applications. (15th July 2019) - Lu, Dan; Han, Qilong; Zhang, Kejia; Zhang, Haitao; Gull, Bisma
Abstract : Location-based services have become a mainstream in people's daily lives due to continuous innovations in the field of mobile networking and GPS technologies. Recently they have advanced into a hot topic to which the majority of researchers pay close attention about how to enjoy them while safeguarding the location privacy of mobile users. Existing works involve the injection of random noise that cannot pledge the quality of service. Herein this manuscript, we propose a novel location privacy protection model based on the loss of service quality. This model allows the user to express his/her requirement of service quality by specifying the maximum service quality lossL m a x, which is the user's tolerance.L m a x can be set to 0. Our comprehensive experimental evaluation using a real-world dataset demonstrates that our modus outdoes other state-of-the-art approaches.